2022
DOI: 10.1111/eci.13821
|View full text |Cite
|
Sign up to set email alerts
|

Positive airway pressure therapy in heart failure patients comorbid with obstructive sleep apnea: Cardiovascular outcomes and nighttime‐duration effect

Abstract: Background Comorbidity of obstructive sleep apnea (OSA) and heart failure (HF) is becoming increasingly common. This is a global analysis of positive airway pressure (PAP) efficacy for the cardiovascular outcomes in those HF Patients with comorbid OSA. Methods Related randomized controlled trials were included. Analysed indicators covered primary outcomes (cardiac function, motor ability and life quality) and secondary outcomes (blood pressure and OSA‐accompanying symptoms). Weighted mean difference was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The complex shared and causal associations may help partially explain the inconsistent evidence of treatment benefit for several cardiometabolic phenotypes with OSA treatment. 59 , 60 , 61 , 62 , 63 Our findings of a causal effect of diabetes (particularly HbA1c) on OSA is consistent with recent reports from longitudinal cohort studies, 64 and may reflect the effects of glucose dysregulation on upper airway function or body fat distribution. There are some experimental evidences from studies in rats, supporting the suggestive causal association of BP on OSA: one study reported a reduction in apnoea events followed by induction of hypotension.…”
Section: Discussionsupporting
confidence: 90%
“…The complex shared and causal associations may help partially explain the inconsistent evidence of treatment benefit for several cardiometabolic phenotypes with OSA treatment. 59 , 60 , 61 , 62 , 63 Our findings of a causal effect of diabetes (particularly HbA1c) on OSA is consistent with recent reports from longitudinal cohort studies, 64 and may reflect the effects of glucose dysregulation on upper airway function or body fat distribution. There are some experimental evidences from studies in rats, supporting the suggestive causal association of BP on OSA: one study reported a reduction in apnoea events followed by induction of hypotension.…”
Section: Discussionsupporting
confidence: 90%
“…Whether CPAP improves MetS is a very controversial issue. Several studies have demonstrated that long‐term and high‐adherence CPAP therapy has beneficial effects on insulin resistance, impaired glucose tolerance, and cardiac function 17,40 . Another study showed that CPAP treatment significantly increased insulin secretion and decreased circulating leptin, LDL cholesterol, and total cholesterol 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that long‐term and high‐adherence CPAP therapy has beneficial effects on insulin resistance, impaired glucose tolerance, and cardiac function. 17 , 40 Another study showed that CPAP treatment significantly increased insulin secretion and decreased circulating leptin, LDL cholesterol, and total cholesterol. 41 In addition, a most recent study also demonstrated that 6 months of CPAP therapy in patients with OSA promoted a higher chance of MetS reversal as compared with a placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous articles have been published detailing the interaction mechanisms between OSA and CVD. It is generally accepted that OSA‐induced changes in hypoxaemia, oxidative stress, sympathetic activation, and decreased intrathoracic pressure can induce or exacerbate a number of CVDs by altering myocardial electrical conduction, damaging cardiomyocytes and endothelial cells, increasing heart rate and blood pressure, and promoting ventricular remodelling (Di Fusco et al, 2020; Fei et al, 2022; Ifedili et al, 2022; Lin et al, 2022; Yeghiazarians et al, 2021). In turn, CVD causes or exacerbates OSA mainly due to factors such as hypervolaemia (Lyons & Bradley, 2015), fluid redistribution during sleep (Lyons & Bradley, 2015), and a sudden increase in blood pressure (Garpestad et al, 1992) that leads to the collapse of the upper airway.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, the impact of OSA and cardiovascular co‐morbidity is snowballing, making the search for more effective measures to interrupt the association a hot topic. Despite the proliferation of relevant studies, an extensive search revealed that existing studies have only focussed on exploring the impact of OSA treatment (such as continuous positive airway pressure) on various co‐morbidities (Li et al, 2022; Lin et al, 2022), with little mention of how the treatment of co‐morbidities affects the development of OSA. There is also a lack of specific treatment recommendations for co‐morbidities in the relevant clinical guidelines (Epstein et al, 2009; Randerath et al, 2021; Veasey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%